Students’ Emotional Well-Being, and Perceived Faculty Incivility and Just Behavior Before and During COVID-19 - Alt, Dorit; Itzkovich, Yariv; Naamati-Schneider, Lior (Frontiers in Psychology, 2022)
This research set out to measure the impact of the lockdown condition and social distancing imposed on higher education by the Israeli government during the COVID-19 period and the shift to online learning, on students’ emotional well-being, the way they perceived their teachers’ just behavior, and faculty incivility, compared to pre-pandemic conditions. An additional aim was to explore the set of connections among these factors. The total sample included 396 undergraduate students from three academic colleges. Data were gathered via three questionnaires: Positive/negative affect, Faculty Incivility, and Teacher Justice. Data were analyzed using Partial Least Squares - Structural Equation Modeling. The main finding showed that students’ negative emotions were informed by the lockdown condition. This perceived negative affect had an impact on how the participants experienced social interactions with their faculty. Those who exhibited higher levels of negative affect perceived themselves as targets of faculty incivility. The same trajectory was detected with the way students experienced their teachers’ just behavior. Students who held negative emotions, partly because of the COVID-19 restrictions, also viewed their teachers’ behavior towards them as unjust. This study stresses the role of one’s emotional condition in instigating negative interpretations of social interactions. Directions for subsequent research and practical implications for promoting students’ well-being and civil and just communications in the learning environment are discussed.